LEGALITAS PENGGUNAAN TENAGA NUKLIR SEBAGAI PEMBUATAN PERSENJATAAN MILITER DARI SUDUT PANDANG HUKUM INTERNASIONAL - Hapsari, Murti Ayu (UIR Press, 2024)
Nuclear power is a form of energy that has many benefits such as being able to become a power plant, being one of the energies for war carriers, being the standard charter for making nuclear bombs, besides that Nuclear itself is still pro and con in its use and utilization. lir as it can be used as an energy source for electricity generation. This research uses normative juridical research methods in which normative juridical research focuses on nuclear energy laws and regulations, international conventions, and the laws of the Republic of Indonesia, so as to obtain a clearer picture. Collecting data from several reference books or from journals via the internet, after the data that has been obtained has been collected, it is then discussed and given an explanation in accordance with the applicable provisions so that the final results can be concluded. The results of research on the Legality of the use of nuclear energy as the use of military weapons from the point of view of international law show that the legality of the use of nuclear energy as the use of military weapons can be permitted if it fulfills the principles of the use of nuclear energy and the consideration of the Nuclear Energy Council so that the use of nuclear power cannot harm or become a threat to other countries in the interest of a country.